Constituent power and the legitimacy of international organizations : the constitution of supranationalism - Oates, John G. (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book develops a constitutional theory of international organization to explain the legitimation supranational organizations. Supranational organizations play a key role in contemporary global governance, but recent events like Brexit and the threat by South Africa to withdraw from the International Criminal Court suggest that their legitimacy continues to generate contentious debates in many countries. Rethinking international organization as a constitutional problem, Oates argues that it is the representation of the constituent power of a constitutional order, that is, the collective subject in whose name authority is wielded, which explains the legitimation of supranational authority. Comparing the cases of the European Union, the World Trade Organization, and the International Criminal Court, Oates shows that the constitution of supranationalism is far from a functional response to the pressures of interdependence but a value-laden struggle to define the proper subject of global governance"--
OCLC-licensed vendor bibliographic record.
Keywords: International organization; Supranationalism; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / General